Social Context of Implementing the National System of Teacher Development in Russia: Teachers' Awareness - Margolis A.A; Novikova E.M (Moscow State University of Psychology and Education, 2017)
The article is based on the results of the research conducted by the Center for Applied Psychological and Pedagogical Studies of the Moscow State University of Psychology and Education in 2016 and is devoted to the analysis of awareness and attitude of Russian teachers to the national system of teacher development.The study was carried out within the whole country; 838 teachers from 9 federal districts were surveyed.The results showed that a Russian teacher has little awareness about the national system of teacher growth (NSTG).At the same time, the level of awareness largely determines the attitude towards the implementation of NSTG.In general, Russian teachers have indicated a positive attitude towards the implementation of a horizontal hierarchy of positions, however, they are not certain that the new model would provide them with new opportunities for career growth.This article assesses the readiness of schools to move to a new system and the likely consequences of such a move, according to the opinion of the direct participants of the process - teachers from general education schools.